Knowledge and Awareness of Root Canal Treatment among Patients in Tripoli: A Survey-Based Study - Sumaya Aghila (AlQalam Journal of Medical and Applied Sciences, 2024)
Root canal treatment is a branch of dentistry concerned with the morphology, physiology, and pathology of the human dental pulp. The majority of patients worry about a root canal because they don’t know much about it and believe the procedure will is painful. The aim of this study was to assess the knowledge and awareness of patients in a sample of Tripoli Libya’s patients regarding root canal treatment. A Questionnaire comprised 19 questions was distributed in hard copies to 134 patients in public and private dental centers in Tripoli, Libya. The data were then subjected to statistical analysis using Chi square test and Fisher exact test, and P < 0.05 was considered statistically significant. The survey found that 79.9% of patients were familiar with root canal treatment and a significant proportion of patients (80.6%) thought the therapy was necessary for treating tooth pain. There have been statistically significant results linking endodontic professionals’ experiences with different age groups. Similarly, a significant connection has been shown between patient’ knowledge about root endodontic therapy and their level of education. Additionally, women’s decisions to receive treatment are significantly influenced by the cost of treatment. According to our study, it was clear that most of the people had good knowledge and awareness regarding root canal treatment, but they felt it was costly. A general dentist was the first choice for the majority of patients. The cost associated with treatment was a serious barrier to obtaining treatment, especially among women. علاج قناة الجذر هو فرع من طب الأسنان يهتم بمورفولوجيا وفسيولوجيا وأمراض لب الأسنان البشرية. يشعر غالبية المرضى بالقلق بشأن علاج قناة الجذر لأنهم لا يعرفون الكثير عنها ويعتقدون أن الإجراء سيؤلمهم. وقد كان الهدف من هذه الدراسة هو تقييم معرفة ووعي المرضى في عينة من مرضى طرابلس, ليبيا فيما يتعلق بعلاج قناة الجذر.تم توزيع الاستبيان في نسخ ورقية على 134 مريضا في مراكز طب الأسنان العامة والخاصة في طرابلس. يتألف الاستبيان المستخدم في الدراسة من 19 سؤالاً يتعلق بالحاجة إلى علاج قناة الجذر وعوامل مختلفة، بدءًا من المعلومات الشخصية والعامة إلى أسئلة محددة حول معرفة المرضى وموقفهم وفهمهم لمعالجة قناة الجذر. تم بعد ذلك إخضاع البيانات للتحليل الإحصائي باستخدام اختبار مربع تشي واختبار فيشر الدقيق، واعتبرت قيمة P<0.05 ذات دلالة إحصائية. وجد الاستطلاع أن 79.9% من المرضى كانوا على دراية بعلاج قناة الجذر وأن نسبة كبيرة من المرضى (80.6%) اعتقدوا أن العلاج ضروري لعلاج آلام الأسنان. كانت هناك نتائج ذات دلالة إحصائية تربط بين تجاربهم مع المتخصصين في علاج قناة الجذر لمختلف الفئات العمرية. وبالمثل، فقد ظهر وجود علاقة هامة بين معرفة المرضى حول علاج قناة الجذر ومستوى تعليمهم. وأظهرت المعلومات أنه بعد علاج قناة الجذر. علاوة على ذلك، فإن المؤشر الوحيد المهم لجوانب تلقي علاج قناة الجذر التي كانت الأكثر إيلامًا أو قلقًا هو العمر. بالإضافة إلى ذلك، تتأثر قرارات النساء لتلقي علاج قناة الجذر بشكل كبير بتكلفة العلاج.وفقا لدراستنا، كان من الواضح أن معظم الناس لديهم معرفة ووعي جيدين فيما يتعلق بمعالجة قناة الجذر، لكنهم يعتقدون أن العلاج مكلف. وقد كان طبيب الأسنان العام هو الخيار الأول لغالبية المرضى. كانت التكلفة المرتبطة بمعالجة قناة الجذر عائقًا قويا أمام الحصول على العلاج